Agroclimatic classification on the basis of moisture availability index and its application to the dry farming tract of Gujarat - BISWAS, B. C. (MAUSAM, 1982)
Weekly Moisture Availability Index (MAI) at different probability levels has been calculated at 81 stations in the dry farming tract of Gujarat. This tract has been divided into four agroclimatic zones, i.e., D, E, F and G on the basis of MAI at 50 per cent level. The zone D is the low crop potential area where rainfed crops are possible in 30-40 per cent of the years. A short duration crop may be grown from area Eat 40-50 per cent of occasions. Area F has the potential to grow crops 50-55 per cent of years. Rainfed crops may be raised in 60 per cent of the years from area G. Moisture availability index at 40, 60 and 70 per cent levels have also been computed to find out agricultural potential at different risk levels. From this analysis, it is possible to identify the core of low crop potential area and time of life saving irrigation. Crop prospect of one station at each zone at various risk levels has been discussed, taking into account the water stress period, type and depth of soil.